Kebutuhan Alat dan Mesin Pertanian serta Investasi untuk Meningkatkan Produktivitas Beras di Kabupaten Ogan Komering Ulu Selatan - Hasbi Hasbi; Tri Tunggal; Olivia Ritanty (Seminar Nasional Lahan Suboptimal, 2021)
Hasbi H, Tunggal T, Ritanty O. 2021. The needs of agricultural tools, machinery and investment to improve the productivity of rice in south Ogan Komering Ulu Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 670-681. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The purpose of this research was to find out the amount of agricultural tools and machinery and the invesment incurred to procure agricultural equipment and machinery required to improve the production of rice in the regency of South OKU, South Sumatra province. The research was carried out on Juni until October of 2019 at Department of Agriculture of South Ogan Komering Ulu Regency, Food Security Service of South Ogan Komering Ulu, UPJA (Agricultural Equipment and Machinery Services Unit), Gapoktan (Farmer Groups Union) in BPR Ranau Tengah, Buay Runjung, and Muaradua Kisam sub-district of South Ogan Komering Ulu Regency. This research used a descriptive method with tabulation presentation. The parameters used in this research were the number of Agricultural Equipment and Machinery, the level of Agricultural Equipment and Machinery sufficiency and the cost of investment. The result of this research has shown that the distribution of Agricultural Tools and Machinery was still very deficient and not evenly distributed. Two-wheel tractor and rice transplanter showed the percentage of 73% or in medium category, four-wheel tractor in percentage of 100% or in sufficient category and the agricultural tools and machinary in deficient category with percemtage under 40% includes combine harvester, power thresher and vertical dryer. Most sub-district in South OKU have not yet received any equipment, the sub-district that received it have insufficient number of equipment. The total investment cost to be incurred to satisfy agricultural equipment and machinery requirement in South OKU regency was 39,889,500,000 IDR.